Analog of the Weierstrass Theorem and the Blaschke Product for A(z)-analytic Functions - Ne'matillayeva, Muhayyo; Khursanov, Shohruh (Journal of Siberian Federal University. Mathematics & Physics, 2023)
We consider A(z)-analytic functions in the case when A(z) is an antiholomorpic function. For A(z)-analytic functions analogs of the Weierstrass theorem and of the Blaschke theorem are proved.